Negotiating Intra-Muslim Diversity: Social Cohesion, Cultural Negotiation, and Ahmadiyah–Non-Ahmadiyah Coexistence in Tenjowaringin, West Java - Maulana Janah; Mokhamad Sukron; Mahbub Setiawan; Dadan; Faiz Husaini (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This study examines the production of intra-Muslim social cohesion in Tenjowaringin Village, Tasikmalaya Regency, where members of Jemaat Ahmadiyah Indonesia (JAI) constitute a local demographic majority while remaining marginalized at the national and provincial levels. It investigates how residents negotiate theological boundaries, which everyday institutions sustain cooperation, and how state regulation and external mobilization shape local coexistence. This qualitative case study was conducted through multiple field visits between June 2025 and March 2026. Data were generated through face-to-face interviews with seven participants, including village officials, JAI figures, an NU cleric, a youth representative, non-JAI residents, and two women participants; field observation; and analysis of village documents. Interviews lasted approximately one hour, were recorded and documented, and were subsequently checked with key participants. The findings identify five interrelated mechanisms: the pragmatic bracketing of doctrinal disagreement; the activation of Sundanese moral idioms and gotong royong; cross-affiliation kinship; economic interdependence; and the role of religious leaders and the village government in normalizing cooperation. Cohesion in Tenjowaringin is not the absence of theological difference but an ongoing negotiated social compact. The village head estimated that approximately 3,500 of 5,362 residents were affiliated with JAI, demonstrating that majority-minority positions shift across scale: JAI is locally influential yet structurally vulnerable. The article develops negotiated cohesion as a form of hybrid solidarity that combines cultural habitus, bonding and bridging social capital, and lived religion.